Understanding the lived experience research priorities for improving health-related quality of life in people living with HIV with cognitive impairment - Kate Alford; Jaime H. Vera; John Hammond; Stephanie Daley (HIV Research & Clinical Practice)
Background People living with HIV experience higher rates of cognitive impairment (CI), and at younger ages, than the general population. These individuals report poor health-related quality of life (HRQL), however, interventions aimed at assisting people living with HIV to live well with CI do not currently exist and represent an important un-met need in this population. Objective This study aimed to identify the lived experience research priorities for improving HRQL and identify interventions to support priority areas. Methods A Research Advisory Group was established with 15 lived experience, academic, healthcare, and third sector professionals. Additionally, two semi-structured focus groups were undertaken, with health and third sector professionals and people living with HIV with CI. Participants were asked to rank factors impacting HRQL, identified in prior research, in terms of priority and intervention development. Findings were analysed using a combination of conventional and summative content analysis. Study findings were feedback to our Research Advisory Group. Results Five people living with HIV with CI, recruited through third sector agencies [Male 80%; median age 59 (range 56–78); White British 60%; homosexual 60%], and three healthcare and third sector participants (66% third sector professionals from two local HIV charities; 33% HIV-specific clinical psychologist) took part in two focus groups and ranked interventions targeting improvement in physical function, social connectedness, cognition and perceived control over cognitive health as priority areas. Findings were then fed back to the Research Advisory Group who recommended the development of an illness-specific cognitive rehabilitation programme and improved information provision as important avenues for intervention development. Conclusion Given the absence of meaningful patient and public involvement, intervention, and support guidelines for people living with HIV with CI, this provides a roadmap for future research in this important and growing area of HIV clinical care.